69 NOVEL THERAPIES FOR RESISTANT FOCAL SEGMENTAL GLOMERULOSCLEROSIS: A PHASE I STUDY. (1st March 2006) - Trachtman, H.; Way, A.; Gipson, D.; Morris, A.; Mitchell, M.; Joy, M.; Bozik, K.; Greene, T.; Gassman, J.
Abstract : Background: Primary focal segmental glomerulosclerosis (FSGS) accounts for 10-15% of pediatric and adult patients with end-stage renal disease. The prognosis is poor in patients who are unresponsive to corticosteroids. The NIDDK has initiated a multicenter, randomized clinical trial comparing the efficacy of cyclosporine versus the combination of mycophenolate mofetil and oral dexamethasone pulses in this patient cohort. Some prevalent patients will be ineligible because of prior treatment with the study drugs and others will fail to respond to the test medications. Their long-term outcome may be improved by therapeutic strategies that reduce progressive glomerulosclerosis and tubulointerstitial fibrosis. Objective: To conduct a phase I study to assess pharmacokinetic (PK) parameters, safety, and tolerance of novel agents that may reduce renal fibrosis in patients who are screen or treatment failures in the FSGS-Clinical Trial. Patients and Methods: Patients, age 2-42 years, GFR 40 mL/min/1.73 m 2, biopsy-confirmed FSGS, and who are screen or treatment failures in the FSGS-clinical Trial are eligible for inclusion. Two novel agents are being tested: (1) rosiglitazone, 3 mg/m 2, daily, PO, and (2) adalimumab, 24 mg/m 2, every other week, SC injection. The treatment phase is 16 weeks with PK evaluation prior to first dose and at end of treatment. DNA, plasma, serum, and urine samples will be obtained for storage in the NIDDK FSGS Biorepository. The study is being performed at sites with an NCRR-funded GCRC. Results: The Manual of Operations and Clinical Report Forms have been written and are posted on the FSGS study Web site (<www.fsgstrial.org >). IRB and GCRC approval has been obtained at 4 sites and is pending at 8 sites. One 18-year-old male adolescent has been enrolled. The target sample is 20 patients, 10 assigned to each agent. Conclusion: This phase I clinical trial represents an important step in improving the treatment of resistant FSGS. The results of this phase I studies will be incorporated into phase II clinical trials as part of a Phased Innovation Award. This project will establish an infrastructure that will facilitate the evaluation of novel agents that reduce renal fibrosis and improve the prognosis in patients with resistant primary FSGS. Support provided by grants from the NIH (DK70341) and the NSLIJ Research Institute General Clinical Research Center, Grant # M01 RR018535.